2014
DOI: 10.1042/an20120041
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-Responsive Progenitors Persist in the Subventricular Zone across the Lifespan

Abstract: The SVZ (subventricular zone) contains neural stem cells and progenitors of various potentialities. Although initially parsed into A, B, and C cells, this germinal zone is comprised of a significantly more diverse population of cells. Here, we characterized a subset of postnatal PRPs (PDGF-AA-responsive precursors) that express functional PDGFα and β receptors from birth to adulthood. When grown in PDGF-AA, dissociated neonatal rat SVZ cells divided to produce non-adherent clusters of progeny. Unlike the self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 68 publications
(99 reference statements)
0
6
0
1
Order By: Relevance
“…derived from this analysis include "Circadian clock", which has not previously been described as a regulator of oligodendrogenesis, although an earlier study proposed this pathway as a cell-intrinsic timer for inhibiting cell division in postnatal OPCs (Gao, Durand, & Raff, 1997). Interestingly, PDGF signaling was uniquely enriched in OLpNSCs in our analysis and we predict that this oligodendrocyte lineage stage comprises the SVZ cell population previously reported to undergo in vivo expansion upon exposure to infused PDGF-A (Jackson et al, 2006;Moore, Bain, Loh, & Levison, 2014). Pathways detected in aNSC and TAP populations comprise "Cell cycle", "DNA/nucleotide synthesis" and "Transcriptional machineries", consistent with single cell profiling studies of adult neurogenesis (Dulken et al, 2019;Llorens-Bobadilla et al, 2015).…”
Section: Discussionmentioning
confidence: 62%
“…derived from this analysis include "Circadian clock", which has not previously been described as a regulator of oligodendrogenesis, although an earlier study proposed this pathway as a cell-intrinsic timer for inhibiting cell division in postnatal OPCs (Gao, Durand, & Raff, 1997). Interestingly, PDGF signaling was uniquely enriched in OLpNSCs in our analysis and we predict that this oligodendrocyte lineage stage comprises the SVZ cell population previously reported to undergo in vivo expansion upon exposure to infused PDGF-A (Jackson et al, 2006;Moore, Bain, Loh, & Levison, 2014). Pathways detected in aNSC and TAP populations comprise "Cell cycle", "DNA/nucleotide synthesis" and "Transcriptional machineries", consistent with single cell profiling studies of adult neurogenesis (Dulken et al, 2019;Llorens-Bobadilla et al, 2015).…”
Section: Discussionmentioning
confidence: 62%
“…These were the CD133+LeX+NG2-CD140a-(NSC), CD133-LeX+NG2-CD140a-(MP1), CD133+LeX+NG2+ CD140a-(MP2), CD133+LeX+NG2+CD140a+ (MP4) and CD133-LeX+NG2+CD140a+ (referred to as PDGFR -FGF2-responsive MPs: PFMP). This PFMP is likely the NG2+ multipotential progenitor that has been isolated from the embryonic forebrain [54] and is similar to the PDGF responsive progenitors present in the neonatal rat SVZ as described by Moore et al, 2014 [57].…”
Section: Multipotential Progenitors Within the Neonatal Svzmentioning
confidence: 52%
“…Another major difference in our method for culturing mouse OPCs was to decrease their exposure to oxygen. Our previous studies have shown that neural progenitor cell proliferation and differentiation can be affected by growth in 20% vs. 2% oxygen incubators [52]. Yet other studies have shown that oxygen tension is a critical determinant in NSC propagation whereas growth in 5% O 2 expanded Nestin+/CD133+/CD24+ precursors that readily differentiated into all three neural lineages [38,39].…”
Section: Discussionmentioning
confidence: 99%